2015
DOI: 10.4293/jsls.2014.00097
|View full text |Cite
|
Sign up to set email alerts
|

Management of Renal Cysts

Abstract: Background and Objectives:Renal cysts have a high prevalence in the general population, and their estimated incidence increases with age. Renal cyst aspiration (usually with sclerotherapy) or open/laparoscopic decortication is a generally effective and safe method in the treatment of symptomatic simple renal cysts. The success rates of laparoscopic decortication and percutaneous aspiration-sclerotherapy were compared to assist in the decision making for the procedure.Methods:A total of 184 patients with sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
5
42
1
2
Order By: Relevance
“…Studies reported by Ali et al [20] and Monville et al [19] evaluated the efficiency of ultrasound-guided AS treatment among patients with renal cysts, their results showed that the radiological successful rate were up to 98% and 91.6% respectively meanwhile the complication and recurrence leveled off to zero. However, the rates of radiological success reported by Efesoy et al [11] and Bas et al [12] were 63.2% and 60% separately, which were also presented in Table 2. Ethanol contacting the cyst wall causes protein degeneration, cell death as well as inflammatory fibrosis so that patients should keep 5 to 10 minutes at least in each position according to the diverse cyst size and volume.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Studies reported by Ali et al [20] and Monville et al [19] evaluated the efficiency of ultrasound-guided AS treatment among patients with renal cysts, their results showed that the radiological successful rate were up to 98% and 91.6% respectively meanwhile the complication and recurrence leveled off to zero. However, the rates of radiological success reported by Efesoy et al [11] and Bas et al [12] were 63.2% and 60% separately, which were also presented in Table 2. Ethanol contacting the cyst wall causes protein degeneration, cell death as well as inflammatory fibrosis so that patients should keep 5 to 10 minutes at least in each position according to the diverse cyst size and volume.…”
Section: Discussionmentioning
confidence: 74%
“…As for the heterogeneity, sensitivity analysis was conducted and delineated in Fig3. In the study of Bas et al [12], the difference of treatment techniques may contribute to the heterogeneity in symptomatic successful rate. Besides, in terms of complication rate, the researches of Agarwal et al [14] and Shao et al [13] only recorded some severe complications such as port infections so that they might omit some information about complications after aspiration treatment, which also brought about the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of simple renal cyst (SRC) is between 20-50% in the general population and the incidence of the condition increases with age. 9 Researchers from Korea reported that the renal cyst prevalence was 2.5% and 1.4% under the age of 40 and increased to 30.1% and 18.3% aged more than 70 years in male and female patients respectively. 10 The general prevalence of renal cyst was 7.8% in all participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although SRCs are common in the general population they are diagnosed incidentally and the clinical presentations include pain, hematuria, hypertension and urinary system obstruction. 9 Surgical treatment is needed when the patients are symptomatic. Percutaneous aspiration, open surgery and laparoscopic techniques are the treatment modalities.…”
Section: Discussionmentioning
confidence: 99%